If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 = 5x + 27 Reorder the terms: -6 + 2x = 5x + 27 Reorder the terms: -6 + 2x = 27 + 5x Solving -6 + 2x = 27 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 2x + -5x = 27 + 5x + -5x Combine like terms: 2x + -5x = -3x -6 + -3x = 27 + 5x + -5x Combine like terms: 5x + -5x = 0 -6 + -3x = 27 + 0 -6 + -3x = 27 Add '6' to each side of the equation. -6 + 6 + -3x = 27 + 6 Combine like terms: -6 + 6 = 0 0 + -3x = 27 + 6 -3x = 27 + 6 Combine like terms: 27 + 6 = 33 -3x = 33 Divide each side by '-3'. x = -11 Simplifying x = -11
| 2y^2-7y-10=0 | | 4x-2(.50-1)=14 | | 101(87+13)= | | y^3+729= | | 4x-2(x-2)=-7+4x+5 | | 9x-12=84 | | 4(2x-3)=30 | | 15-12z=21 | | .17(x-29)=86 | | 2x=1-5 | | 7(x+2)=5(x+14) | | p-4=-1+2P | | 4m+8m=84 | | 2(m-8)=12 | | 9k(8k+7)= | | 10x+44=2(8x-23) | | T+4=120 | | 10-2x=-2y | | 77x^2-145+50= | | 9(x-7)+54=9x-8 | | 2(m-8)=54 | | 16-n=2n+8+5n | | 48+3x=246-15x | | 6x+4=1x-11 | | 7x-20=4x+30 | | 3(x+9)=60 | | 7+2x-10=x+2 | | 105+9.50r=14.75r | | 3x-3+5x-7=5x+3x+10 | | 3x-10=1x+4 | | 2(x+6)=-6x+2 | | 4(c+3t)=x |